HUKUM ISLAM DALAM KERANGKA PEMBARUAN HUKUM PIDANA DI INDONESIA, DILIHAT DARI PERSPEKTIF TEORI HUKUM PEMBANGUNAN MOCHTAR KUSUMAATMADJA - Irawan, Aris (Alhurriyah, 2019)
Development Law Theory refers to the life view (way of life) of Indonesian society based on the principle of Pancasila which encourages kinship then to norms, principles, institutions and rules. Updating laws is part of and at the same time implements punishment. Islamic Judicial Law, specifically concerning Role Law, stoning law for adulterers, as well as qishash, often gets a sharp spotlight from Non-Islamic societies such as Orientalists, as well as research, principles, legal laws and others required in the substance of the Criminal Code, actually regulated and applied in Islamic Law. On the other hand Islamic law in transition is not as rigid as imagined by Orientalists, but is instead flexible and can be used as a source of renewal of the National Criminal Law.